EFFECTS OF USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTS) ON FARMERS’ AGRICULTURAL PRACTICES AND WELFARE IN ORLU AGRICULTURAL ZONE OF IMO STATE, NIGERIA - Chikaire, J. U.; Anaeto, F. C.; Emerhirhi, E.; Orusha, J. O. (UDS International Journal of Development, 2017)
Abstract The aim of this study was to ascertain the effects of the use of Information and Communication Technologies (ICTs) on farmersâ€™ agricultural practices and welfare in Orlu Agricultural Zone, Imo State. Data were collected with structured questionnaire distributed to 130 respondents randomly selected from the 10 extension blocks in Orlu Agricultural Zone. Percentages, bar graphs, mean scores, standard deviation, presented in frequency table and Likert type scale were used to analyze the data. The result obtained showed that ICT devices available in the area included radio, mobile phones, television, and newspapers among others. However, radio is the most readily available ICT device (99.2%), followed by mobile phone (97.7%). It was also observed that ICTs have significant effects on the farmersâ€™, agricultural practices and welfare as indicated by a high mean score on the statements. Several factors constrained the use of ICT devices. Among these factors were erratic power supply (98.5%), low level of education (93.1%), language barrier (92.3%), lack of ICT skills (91.5%), low income of farmers (88.5%), unavailability of ICT centers (82.3%) and high cost of ICT facilities (79.2%). This study thus recommended that Government should provide financial support to farmers through the provision of interest free loans to enable them acquire and use the technologies. Government should improve rural infrastructures particularly electricity supply in the study area. The rural dwellers should be given the requisite skills required for information management. They should be exposed to practical computer training for the enhancement of ICT use. Keywords â€“ ICTs, Farmers, Welfare, Agriculture, NigeriaÂ